Effect of lunar cycle on rainfall (MAUSAM, 1995)
ABSTRACT. Rainfall data for a period of 50 years from 1931 onwards have been analysed for three west, coast stations in Kerala for the southwest monsoon period, The period is divided into two halves, the first half, i.e.June-July, providing comparatively more rainfall  and the second half, i.e. August-September, providing comparatively lesser rainfall. Rainy days, having rain amounts>6.25 cm/day, have only been utilized for this study. The lunar cycle, which is having 29.53 days, is divided into ten phases, each phase constituting of around three days. To consider the effect of solar activity, the period is divided into active and quiet sun by considering those years with sunspot number greater than the upper quartile and those with sunspot number less than the lower quartile respectively. The data were analysed using x2 test. It describes the magnitude of the discrepancy between theory and observation.Analysis has shown that there is some statistical significance between heavy rainfall and lunar cycle. The effect is more significant in active sun period which shows the effect of solar activity also.